(untitled) (Empresa y Sociedad, 2024)
Globally an increased awareness for the preservation of the planet is perceived. Different strategies are being held by countries in order to minimize problems such as pollution, access to vital resources, a responsible disposal of waste, and others. Part of this problem are the industries that generate pollution through the resources they exploit or directly through their waste. This study presents six different companies, conveniently selected in El Salvador, that include green initiatives into their business core in order to minimize the negative impact of their processes over the environment. They are well-known companies and stand out for the quality of their work. The research is qualitative, the methodology used to perform it was descriptive. The information collected from different sources guided the analysis of the theme in order to provide the guideline to the creation of the industrial recycling cluster in El Salvador. In order to propose the cluster, the researchers used Porter´s Diamond Model and the Five Forces Analysis. The results show that there are several advantages for the establishment of a cluster, such as, technology, training, internal resources within the companies, and others. On the other hand, the cluster will need more support from the government, communities and the citizens since most of the problems are due to the lack of regulations and the recycling culture in the population.